TENTANG PELAPUKAN KAPAL KAYU - Ahmad, Muchtar; Nofrizal, Nofrizal (Jurnal Perikanan dan Kelautan, 2009)
A survey and experiment have conducted on fishing boat materials of justconstructed, 10 years and 15 years old. Materials were sampled and its strength wastested in order to understand the fatigue and its cause. The fatigue of materials is inregression linear but depending on the kind of wood, its processing, and the placeused in the boat construction. Those of materials use to be submerged in the waterwill be fatigue faster compare to those used in the dry place. The fatigue caused bymarine organism such sea worm holed into or some mollusks and microbe mashesattach to the surface of wood. Proper processing and well maintenance duringoperation of the boat will makes it be last longer.